J chain synthesis and secretion of hexameric IgM is differentially regulated by lipopolysaccharide and interleukin 5. - Randall, T D (1992)
Two functional polymeric forms of IgM can be produced by antibody-secreting B cells. Hexameric IgM lacks detectable J (joining) chain and activates complement 17-fold better than pentameric IgM, which usually contains one J chain per pentamer. Using the inducible B-cell lymphoma CH12, we determined if the synthesis of a particular polymeric form of IgM is a fixed property of B cells or can be altered. Lipopolysaccharide (LPS)-stimulated CH12 cells produced mixtures of IgM hexamers and pentamers, resulting in antibody with high complement-fixing activity. In contrast, interleukin-5-stimulated CH12 cells secreted predominantly pentameric IgM, with a correspondingly lower lytic activity. Differences in lytic activity were due only to the amount of hexameric IgM in the secreted antibody. Interleukin 5 stimulated higher production of J chain RNA and protein than LPS, while LPS induced the highest levels of the secretory form of mu protein. The amount of hexameric IgM secreted was therefore inversely proportional to the level of intracellular J chain protein in the responding B cells. We conclude that the biologic function of IgM produced by B cells differs depending on how they are stimulated and that this difference may be regulated by the relative availabilities of J chain and secretory mu proteins during IgM polymerization.